OP0023 Targeted Polymeric Nanoparticles as Diagnostic and Therapeutic Tool for Rheumatoid Arthritis. (15th July 2016) - Colombo, F.; Nunez, L.; Durigutto, P.; Biffi, S.; Rampazzo, E.; Belmonte, B.; Sblattero, D.; Gulino, A.; Meroni, P.L.; Tedesco, F.; Macor, P.
Abstract : Background: Rheumatoid arthritis (RA) is a chronic, systemic autoimmune disease affecting joints due to the persistent synovial tissue inflammation. RA treatment has dramatically evolved in the last 20 years due to the production of biological Disease Modifying Antirheumatic Drugs (bDMARDs). However, side effects and the high costs of biological drugs are holding back their widespread usage. Moreover, some patients fail to respond to bDMARDs, for all of these reasons, DMARDs remains the main desired strategy for the treatment of RA, and Methotrexate (MTX) is still the "anchor" drug to treat RA. A successful treatment depends also on the early diagnosis, treating patients as soon as possible to prevent the late stages of the pathology. Objectives: The aim of this work is to develop targeted biodegradable nanoparticles (tBNPs) that could be used as a platform suitable to delivery drugs or diagnostic tracers specifically into the inflamed synovial tissue. This approach usually allows to enhance the efficacy and to reduce the side effects. Methods: We used polymeric biodegradable nanoparticles, made of polylactic acid, polycaprolactone and polyethylene glycol and coated with a peptide characterized for its ability to target only inflamed synovial tissue. The tBNPs diameter was 170 nm with a low negative charge. Toxicity was studied in-vitro assay and in-vivo. Immunofluorescence technique was used to initially assess the ability of fluorescent-tBNPs to preferentially target inflamed synovial tissue. The biodistribution of the nanoparticles and the efficacy of the treatment with tBNPs loaded with MTX were studied in a rat model of antigen-induced arthritis (AIA). Finally, tBNPs efficacy was also studied in a mouse model of collagen-induced arthritis (CIA). Results: Targeted BNPs evidenced the ability to specifically bind inflamed synovial tissue both in vitro and in vivo. The targeting is dependent on the inflammation degree and this highlights the potentiality of the tBNPs as an early diagnostics tools. A single injection of targeted BNPs loaded with MTX completely abrogated the inflammatory process in acute AIA rat model while the same dose of free-MTX was ineffective. Equivalent therapeutic effects were obtained comparing MTX-loaded tBNPs and the same dose of free-MTX in the mouse model of chronic CIA and no toxic effect was documented when MTX was loaded in nanoparticles in these animals. Conclusions: Our results demonstrated that tBNPs can efficiently and selectively delivery drugs and diagnostic probes to inflamed synovial tissue, providing a new platform for an early detection and efficient chronic treatment of inflammatory arthritis, with minimal side effects. Disclosure of Interest: F. Colombo: None declared, L. Nunez Employee of: Biotarget, P. Durigutto: None declared, S. Biffi: None declared, E. Rampazzo: None declared, B. Belmonte: None declared, D. Sblattero: None declared, A. Gulino: None declared, P. L. Meroni: None declared, F. Tedesco: None declared, P. Macor: None declared